Internalising the act of self-regulation : subconscious tactical employment in presenting a politically acceptable self on Facebook. - Siti Sarah Amalina Binte Muhammad Ariff Khoo. (2013)
With Internet campaigning allowed in 2010, Singaporeans have been actively engaging in political discourse on social media in the open despite being in a highly regulated media landscape. Have Singaporeans become indifferent about the constraints posed by social media and thus becoming bolder in speaking up? My research has found that instead most respondents acknowledge these constraints but are not deterred from voicing their political views on their Facebook wall. It therefore seems likely that respondents have been subconsciously regulating themselves to overcome the constraints imposed such that it has become internalised and thus natural. Using a hybrid of elements borrowed from Goffman (1959) and Hogan (2010), my study seeks to uncover and document subconscious tactical employment by users in projecting a politically acceptable self on Facebook in the context of Singapore.